Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Origin Wiracipta Lestari Jakarta Selatan - Azwina, Diana; Lestari, Putri Indah Mei; Piola, Piola (Jurnal Disrupsi Bisnis, 2024)
The purpose of this study is to determine the influence of the work environment and work discipline persely and simultaneously on employee performance at PT. Origin WiraCipta Lestari. The method used is quantitative. The study population numbered 62 people. Analysis techniques and data tests include validity tests and reliability tests, classical assumption tests, linear regression tests, determination tests, correlation tests and hypothesis tests. The results of the partial test of the work environment have a significant effect on employee performance with a calculated value of > t table or (5.264 >2.000) and reinforced with a value of ρ value 0.000 < 0.050. Partially, work discipline has a significant effect on employee performance and the results of the t-value of the t-count > table of (5,823 >2,000). This is also reinforced by the ρ value of 0.000 < 0.050, simultaneously the work environment and work discipline on employee performance at PT Origin WiraCipta Lestari with an F value calculated > F table or (19.164>2.761), and ρ value 0.000 < 0.050.